A bioencapsulation and drying method increases shelf life and efficacy of Metarhizium brunneum conidia. (4th July 2017) - Przyklenk, Michael; Vemmer, Marina; Hanitzsch, Miriam; Patel, Anant
Abstract: This study reports the development of encapsulated and dried entomopathogenic fungus Metarhiuzm brunneum with reduced conidia content, increased conidiation, a high drying survival and enhanced shelf life. Dried beads prepared with the fillers corn starch, potato starch, carboxymethylcellulose or autoclaved baker's yeast, showed enhanced survival with increasing filler content. The maximum survival of 82% was found for beads with 20% corn starch at <0.1 water activity. While increasing starch content inhibits the conidiation, autoclaved baker's yeast and a combination with starch enhanced the conidiation to 1.0 × 10 8 conidia/bead. Beads with conidia content reduced to 0.01% multiplied conidia in a "microfermentation" by the factor 1000. A bioassay confirmed that conidia formed from rehydrated beads were virulent against Tenebrior molitor larvae. After six months of storage, encapsulated conidia showed improved shelf life compared to non-formulated conidia. This "microfermenter" will pave the way for encapsulated fungi to be used as cost-effective biocontrol agents.